The Teaching Chair: Maintaining Excellence in Teaching - Cathy Thorsen 5590686; Mary Elizabeth Zimmer; Marilyn Odom (Academic Chairpersons Conference Proceedings, 2018)
Teaching chairs must balance preparation for class and maintaining teaching effectiveness with the duties of chair. Participants will explore scenarios related to the teaching chair themes derived from survey responses and share strategies for coping, overcoming, and/or accepting their limitations related to balancing chair and teaching roles.
Keywords: Teaching chair; chairperson responsibilities; teaching excellence